THE ROLE OF FEMINISM IN ENGAGING INTERNATIONAL ACTORS TOWARDS EMPOWERING THE EFFORTS OF RECOVERING WOMEN IN POST-PANDEMIC TOURISM - Kartika, Anindya Sekar (Jurnal Multidisiplin Indonesia, 2023)
This study seeks to unravel the role of feminism in shaping the engagement of international actors bilaterally, regionally, and multilaterally in the endeavor to revive and enhance the economic and social condition of women in the tourism industry within the post-pandemic condition. Through the lens of feminism that also perpetuates an understanding from the liberal-institutionalism view, this paper discovers that the engagement of actors who conduct cooperation leading to the establishment of institutions and programs with a focus on the prevailing notion of innovation is underpinned by the salient concept of shared value, which prioritizes the importance of women's rights and gender equality.